2016
DOI: 10.1186/s12903-016-0267-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of early childhood caries and enamel defects in four and five-year old Qatari preschool children

Abstract: BackgroundDental caries is the most prevalent chronic disease in early childhood in most communities worldwide. Several studies conducted in the Gulf Cooperation Council countries have documented a high prevalence of early childhood caries (ECC). To date, no studies have been conducted in Qatar to examine the prevalence of ECC and enamel developmental defects in preschool children. The present study aimed to determine the prevalence of ECC and enamel defects in preschool children aged four and five years atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 27 publications
3
23
0
6
Order By: Relevance
“…This heterogeneity might be due to socioeconomic differences between the study populations or to the study design. The prevalence of DDE in the PTI-G was within the upper range reported in the literature [Oliveira et al, 2006;Franco et al, 2007;Correa-Faria et al, 2013;Masumo et al, 2013;Alkhtib et al, 2016;Wagner, 2016]. The high occurrence of DDE in the PTI-G (65.6%) is consistent with previous comparative studies from Brazil and Spain [Lunardelli and Peres, 2006;Velló et al, 2010;Cruvinel et al, 2012] but higher than in a German local cohort study, where 20.0% of PTI suffered from DDE [Wagner, 2016].…”
Section: Dental Cariessupporting
confidence: 80%
“…This heterogeneity might be due to socioeconomic differences between the study populations or to the study design. The prevalence of DDE in the PTI-G was within the upper range reported in the literature [Oliveira et al, 2006;Franco et al, 2007;Correa-Faria et al, 2013;Masumo et al, 2013;Alkhtib et al, 2016;Wagner, 2016]. The high occurrence of DDE in the PTI-G (65.6%) is consistent with previous comparative studies from Brazil and Spain [Lunardelli and Peres, 2006;Velló et al, 2010;Cruvinel et al, 2012] but higher than in a German local cohort study, where 20.0% of PTI suffered from DDE [Wagner, 2016].…”
Section: Dental Cariessupporting
confidence: 80%
“…A higher caries experience in permanent teeth was observed in the case group compared with the control group, corroborating the results of other studies [1,11,16,19,[37][38][39]. Molar-incisor hypomineralization is a qualitative enamel defect, making teeth more susceptible to dental caries [4,11,16,17].…”
Section: Discussionsupporting
confidence: 89%
“…Demarcated opacities were the most common type of DDE observed in the present study (11.5%), similarly to previous studies . A Brazilian study involving preschool children showed a slightly higher prevalence of demarcated opacities; however, that study involved children who were older than those in our study, different that used in our research.…”
Section: Discussionsupporting
confidence: 88%